Percutaneous coronary intervention of recurrent ostial restenosis in the course of incomplete expansion of two layers of stents – intravascular lithotripsy under guidance of optical coherence tomography - M. Wańczura, Piotr; Rogala, Marcin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Ostial calcified lesions still constitute a challenge in invasive cardiology. The risk for restenosis is relatively high, especially when more than one layer of struts is implanted with a suboptimal result. Ostial in-stent restenosis (ISR) within an underexpanded stent could be a challenge especially if non-compliance (NC) or ultra-high pressure balloons are ineffective. Although intravascular lithotripsy (IVL) is not recommended in in-stent lesions, the off-label usage of IVL could be the only chance to improve the clinical outcome [1]. This technique uses a balloon-mounted ultrasound source leading to emission of sonic pressure waves propagating through the fluid and delivered to the coronary artery wall. It results in the fragmentation of both superficial and deep calcium deposits, allowing better balloon expansion. Intravascular imaging including optical coherence tomography (OCT) may deliver extra information about the pathomechanism of restenosis and the most effective treatment. Performance of percutaneous angioplasty (PCI) under OCT guidance has an established scientific position in ostial lesions and recurrent restenosis [2].